Autolysis and Cell Death Is Affected by pH in L. reuteri DSM 20016 Cells - Tahl Zimmerman; Salam A. Ibrahim (Foods, 2021)
A key obstacle to the successful delivery of a probiotic to the consumer is maintaining viability of the live cells during storage, a challenge for the beneficial Lactibacillus reuteri. Three processes play a role in the reduction of viability: autolysis, cell death, and cell weakening. Using a phosphate induction model of autolysis, the initial aim of this project was to discover novel molecular determinants of autolysis in L. reuteri, with the long -term goal of elucidating new strategies for increasing viability. We employed a 2D Native/SDS-Page method to monitor changes in protein expression over time; however, the result was that excess phosphate did not induce noticeable changes in expression patterns. On the other hand, we found that pH affects both the rate of total viability and autolysis, as seen with other species of LAB. In addition, we found that the phosphate model of autolysis may not be sufficient to explain how autolysis is triggered in L. reuteri. Two parameters appear to modulate the pH in media containing L. reuteri cells: overall buffering capacity and the presence of a carbon source. Ultimately, phosphate sources appear to facilitate autolysis by maintaining pH in the media via a higher buffering capacity. In addition, the alkaline sugar free almond drink appears to be a promising possible preservative for L. reuteri.